Extragenital lichen sclerosus et atrophicus - Leelavathy Ganesan; Heena Parmar; Jayanta Kr Das; Asok Gangopadhyay (Wolters Kluwer Medknow Publications, 2015)
Lichen sclerosus et atrophicus (LSA) is a chronic inflammatory dermatosis with anogenital and extragenital presentations. Extragenital lichen sclerosus is most common on the neck, shoulders and upper trunk. Linear lesions are uncommon in LSA. We report a case of linear extragenital LSA involving forehead and scalp, along with grouped white papules of LSA in the right side of the back in a postmenopausal woman. The patient showed atypical clinical presentation of LSA in face which clinically mimicked 'en coup de sabre' as seen in morphea, but other clinical features suggested the diagnosis of LSA and the histopathological findings confirmed it.